Metacognition impairment in stroke - Tang, Wai Kwong; Hui, Edward; Leung, Thomas Wai Hong (Frontiers in Neurology, 2025)
IntroductionMetacognition (MC) impairment is prevalent among stroke survivors but is frequently undiagnosed and untreated. MC impairment hinders stroke survivors’ ability to recognize their deficits, causing them to engage in activities that exceed their capabilities, set unrealistic performance goals and fail to use adaptive compensatory strategies. The present study will evaluate the clinical, neuropsychological and MRI correlates of MC impairment in a cohort of stroke survivors. The secondary objective is to describe the 12-month course of MC impairment.Methods and analysisThe current study is a prospective cohort study. We will recruit 246 subjects. The project duration is 36 months. Subjects and carers will receive a detailed assessment at a research clinic at three, nine and 15 months after stroke onset (T1/T2/T3). The Chinese version of the Self-Awareness of Deficits Interview (SADI) will be completed by each subject. MC impairment is defined as any SADI subscale score of 2 or more. Potential covariate will be measured as well. Tests of executive functioning will be administered as well. Patients will be examined by MRI within 1 week after the onset of stroke. A stepwise logistic regression will be performed to assess the importance of lesions in the regions of interest. To examine neuropsychological functions in MC impairment, regression analysis of the SADI total and subscale scores will be performed using the significantly correlated neuropsychological functions as predictors. To examine the predictors of MC impairment remission, the demographic, clinical and MRI variables of remitters and non-remitters at T2/T3 will be examined by logistic regression.DiscussionThis project will be the first longitudinal study on MC impairment in stroke survivors. The results will shed light on the association between prefrontal cortex and subcortical lesions and MC impairment risk, symptom severity and outcome.